Genetic admixture increases phenotypic diversity in the nectar yeast Metschnikowia reukaufii. (February 2021) - Álvarez-Pérez, Sergio; Dhami, Manpreet K.; Pozo, María I.; Crauwels, Sam; Verstrepen, Kevin J.; Herrera, Carlos M.; Lievens, Bart; Jacquemyn, Hans
Abstract: Understanding the relationship between population genetic structure and phenotypic diversity is a fundamental question in evolutionary biology. Yeasts display wide genetic diversity and exhibit remarkably diverse heterotrophic metabolisms that allow a variety of niche occupations. However, little is known about how intra-species genetic population structure is related to trait diversity in yeasts. In this study, we investigated the link between intra-species genetic population structure and trait diversity in the floral nectar-inhabiting yeast Metschnikowia reukaufii (Ascomycota). A total of 73 strains obtained from 11 plant species were genotyped by whole genome sequencing, followed by single nucleotide polymorphism (SNP) calling, and phenotyped using a robot-assisted high-throughput screening platform. Analysis of the population structure estimated the number of ancestral populations to be K  = 5, each one including strains from different locations and host plants, and 26% of strains showed significant genetic admixture (<80% ancestry from a single population). These mosaic strains were scattered throughout a maximum-likelihood phylogenetic tree built from SNP data, and differed widely in their ancestry. While yeast strains varied in nutrient assimilation and tolerance to inhibitors, trait differentiation among genetic lineages was in most cases negligible. Notably, outlier phenotypes largely corresponded to the mosaic strains, and removal of these from the data had a dramatic effect on the intra-species phylogenetic signal of studied phenotypes and patterns of trait evolution. Overall, these results suggest that genetic mosaicism broadens the phenotypic landscape explored by M. reukaufii and may allow adaptation to highly variable nectar environments.